Hypnobirthing Efeectiveness on Length Stage of Labor - Bringiwatty Batbual; Hasri Yulianti; Matje Meriati Huru; Namsyah Baso; Umi Kaltsum S. Saleh; Adriana Boimau; Serlyansie Boimau; Jane Leo Mangi (Alliance oh Health Activists (AloHA), 2022)
The first stage of labor begins with regular uterine contractions followed by cervical dilatation and effacement until the cervix is fully dilated. Anxiety, stress and long labor pain during labor can affect uterine contractions, so that it can affect the length of the first stage of labor. Hypnobirthing can be trained during pregnancy and applied by the mother herself during the delivery process which is useful for reducing and overcoming pain and anxiety during labor so that uterine contractions are more adequate and labor can take place in a relaxed, comfortable and brief manner. The purpose of this study was to determine the difference in the length of the first stage of labor between mothers who had hypnobirthing and without hypnobirthing. The design of this study was a clinical trial with a randomized control trial. The independent variable was hypnobirthing and the dependent variable was the length of the first stage. Data were analyzed using Chi-square and independent sample t-test. The results showed that the average length of the first stage with hypnobirthing was shorter (10.09) hours than without hypnobirthing (17.23) hours with a difference of 6.74 hours. Hypnobirthing, if performed at 37-40 weeks of gestation, had a 1.96 times greater effect on decreasing the length of the first stage of labor with an effect strength of 5.7%, statistically and clinically the reduction effect was significant. The conclusion of the study is that the duration of the first stage of labor is shorter than using hypnobirthing compared to without hypnobirthing. Keywords: hypnobirthing; length of labor